2010
DOI: 10.1155/2010/192371
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Features of Eccrine Porocarcinoma Arising from Hidroacanthoma Simplex

Abstract: Eccrine porocarcinoma is a rare cutaneous neoplasm that mainly affects elderly people and grows slowly over a long period of time but often experiences an accelerated growth phase. Eccrine porocarcinoma may arise de novo or evolve from a pre-existing benign eccrine poroma. We reported a 86-year-old Japanese woman presenting with two reddish-colored pendulated lesions on a keratotic light brown plaque on the right thigh. Dermoscopic examination of the light-brown plaque demonstrated many whitish globular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Metastasis is reported to occur in 20% of patients while current review among 36 studies and 61 patients showed that metastasis occur in 26%. The most common affected organ to which EP metastise is lymph nodes (60%) followed by chest (13%), Table 3 shows the involved organs in literatures with their frequency of affection [1], [6], [10], [11], [14], [16], [22], [24], [25], [28], [31], [33], [34]. Our case showed metastasis to lung, cervical lymph nodes and brain.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Metastasis is reported to occur in 20% of patients while current review among 36 studies and 61 patients showed that metastasis occur in 26%. The most common affected organ to which EP metastise is lymph nodes (60%) followed by chest (13%), Table 3 shows the involved organs in literatures with their frequency of affection [1], [6], [10], [11], [14], [16], [22], [24], [25], [28], [31], [33], [34]. Our case showed metastasis to lung, cervical lymph nodes and brain.…”
Section: Discussionmentioning
confidence: 87%
“…[10] Among reported cases, 8th decade of life is the ideal age of affection followed by 7th decade (Table 1). [1], [3], [6], [10], [11], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34] EP does not have predilection for specific part of the body. [24] Arslan et al stated that it tends to involve most frequently in the extremities especially lower limbs, followed by trunk and head while current literature review showed that EP occurs most commonly at the lower limbs (35%) followed by head(24%) and upper limbs (14%) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to seborrheic keratosis, it is possible for eccrine porocarcinoma to develop from HAS [4]. Notably, HAS is sometimes misdiagnosed and treated by cryosurgery as seborrheic keratosis, which could trigger the development of porocarcinoma in the future.…”
Section: Introductionmentioning
confidence: 99%